Internal split liver transplants reduce the waiting list time for teenagers with a low calculated Model for End‐stage Liver Disease score. (27th November 2020) - Lemoine, Caroline; Brandt, Katherine; Carlos Caicedo, Juan; Superina, Riccardo
Abstract: Background: Split liver transplantation allows for the simultaneous transplantation of two patients, typically a child and an adult, with a single organ. We report our experience with "internal splits" in which 10 pediatric patients from our institution were transplanted with five organs. We hypothesized that this would reduce the WL time for teenagers with a low calculated MELD score. Methods: A retrospective chart review of those 10 patients was done. Their WL time was compared with local, regional, and national data. P  < .05 was considered significant. Results: The median age of the five primary recipients to whom the liver was first allocated was 2.3 years (0.7‐7.4) (median weight 10.4 kg (8.4‐17.7)). They received a segment 2‐3 graft. Five "secondary" recipients (median age 17.4 years (16.6‐18.9); median weight 66.2 kg (53.7‐70.0)) were identified on our WL to receive the trisector graft. At transplant, their median calculated MELD score was 11 (8‐20). Their mean WL time (241.6 ± 218.9 days) was significantly shorter than local (480.6 ± 833.6 days), regional (370.4 ± 563.4 days), and national patients (245.6 ± 465.4 days) with MELD ≤ 20 ( P  = .047). There was no significant difference between their WL time and that of patients with a MELD 8 ≤ x≤31 (equivalent to their median exception score, P  = .63). Patient and graft survival was 100% for all 10 patients. Conclusion: In our experience, simultaneous internal split liver transplantation allowed teenagers with a low calculated MELD score to be transplanted faster than patients with a similar score. Promoting the use of internal split liver transplantation could help reduce the pediatric waitlist mortality.